Teologi Wabah Perspektif Ibnu Hajar Al-‘Asqalani dan Slavoj Ẑiẑek - Harjuna, Muhamad (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2021)
This article discussed about the theology of pandemic in the perspective of Ibn Hajar al-'Asqalani and Slavoj Ẑiẑek. The author examined the book Badzlul Ma'ûn fi Fadhli ath-Thā'ûn and the book Pandemic, Covid-19 Shakes the World. This paper is a literature study, namely analyzing text as a source of data in the writing process. The pandemic in Ibn Hajar's perspective based on the hadith is a form of "torment" from God, and originates from the disturbance of the Jinn. Ethics in dealing with the pandemic includes praying qunut, global prayer, a healthy lifestyle and not visiting areas affected by the epidemic, and also not leaving areas that have been hit by the epidemic. Slavoj Ẑiẑek views that there is a need for a fundamental change in the governance of global life, a global ethic that is agreed upon in anticipation of the threat of shocking human life as experienced today.